Sing Down the Moon - O'Dell, Scott (Hamish Hamilton Children's Books Ltd, 1972)
The Spanish Slavers were an ever-present threat to the Navaho way of life. One lovely spring day, fourteen-year-old Bright Morning and her friend Running Bird took their sheep to pasture. The sky was clear blue against the red buttes of the Canyon de Schelly, and the fields and orchards of the Navahos promised a rich harvest. Bright Morning was happy as she gazed across the beautiful valley that was the home of her tribe. She tumed when Black Dog barked, and it was then that she saw the Spanish slavers riding straight toward her. "The forced migration of Navahos from their original homeland in Arizona to Fort Summer, New Mexico, is described from the Indian point of view in a poignantly moving first-person story about Navaho life in the mid-1860's."-THE "Booklist." "Beautifully written, immensely moving, "Sing Down The Moon" is a memorable reading experience--for any age."-Book World. "The very simplicity of the writing, at times almost terse, makes more vivid the tragedy of the eviction and the danger and triumph of the retum. Recommend."-Bulletin of the Center for Children's Books. "An outstanding Book of the Year."- "The New York Times."
Keywords: Juvenile literature-Historical-American Indians-Fiction